A method for synchronously preparing sulfuric acid and cementitious material by using phosphogypsum and aluminum ash

By mixing quicklime, aluminum ash and phosphogypsum and electrolyzed in an electrolytic cell, carbon dioxide gas reaction is used to generate sulfuric acid aqueous solution and gelled materials, the harmless disposal and resource utilization of phosphogypsum and aluminum ash is solved, and efficient and environmentally friendly preparation of sulfuric acid and gelled materials is achieved.

CN115896815BActive Publication Date: 2025-04-18中环联(江西)国际再生资源有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211389663.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2025-04-18
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

The harmless disposal and resource utilization of phosphogypsum and aluminum ash is difficult to effectively solve, resulting in environmental pollution and waste of resources.

Method used

By mixing quicklime, aluminum ash and phosphogypsum, stirring evenly, forming calcium-aluminum phosphogypsum, then mixing with water, stirring to make a slurry, and electrolyzed in an electrolytic cell, the carbon dioxide gas reaction is used to generate a sulfuric acid aqueous solution and gelled material.

Benefits of technology

The high-efficiency preparation of sulfuric acid aqueous solution and gelling materials is achieved. The maximum sulfuric acid mass fraction of sulfuric acid aqueous solution is 43%, the strength of the gelling material can reach 46.79MPa, and it is simple to operate and has low equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896815B_ABST
    Figure CN115896815B_ABST
Patent Text Reader

Abstract

The invention discloses a method for synchronously preparing sulfuric acid and a cementitious material by using phosphogypsum and aluminum ash. The method uses phosphogypsum and aluminum ash as raw materials to synchronously prepare sulfuric acid and a cementitious material. The prepared sulfuric acid aqueous solution has a maximum sulfuric acid mass fraction of 43%, and the prepared cementitious material has a maximum strength of 46.79 MPa. The preparation operation process of the invention is simple and the equipment requirements are low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synchronously preparing sulfuric acid and a gelling material by utilizing phosphogypsum and aluminum ash, and belongs to the field of harmless disposal of solid wastes. Background Art

[0002] Phosphate fertilizer is one of the three major fertilizers, and its production and supply are related to national food security and basic industries for people's livelihood. Phosphoric acid is the basic raw material for phosphate fertilizer production, and phosphoric acid is usually prepared by dissolving phosphate rock with sulfuric acid. In the process of using phosphate rock to generate phosphoric acid, a large amount of phosphogypsum by-product will inevitably be produced. Phosphogypsum is acidic, and its main component is calcium sulfate dihydrate, which contains a small amount of impurities such as phosphorus and fluorine. The storage and leakage of phosphogypsum can easily lead to excessive total phosphorus in groundwater, causing eutrophication of water bodies and affecting the health of the basin ecosystem. Therefore, the industry needs to improve the comprehensive utilization rate of phosphogypsum and expand the utilization of phosphogypsum.

[0003] my country is a major aluminum producer and consumer. A large amount of aluminum ash is easily generated during the production, processing, and recycling of primary aluminum (smelting, electrolysis, and dust removal). Aluminum ash is toxic and reactive. If it is dumped or landfilled without treatment, it will cause serious environmental pollution.

[0004] Therefore, if the synergistic technology of harmless disposal and resource utilization of phosphogypsum and aluminum ash can be developed, it can provide a technical idea that can be used as a reference for solving the problems caused by the above-mentioned phosphogypsum and aluminum ash. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for synchronously preparing sulfuric acid and cementitious materials by using phosphogypsum and aluminum ash.

[0006] Technical solution: The present invention provides a method for synchronously preparing sulfuric acid and cementitious material by using phosphogypsum and aluminum ash, comprising the following steps:

[0007] (1) mixing quicklime, aluminum ash and phosphogypsum, and stirring evenly to obtain calcium aluminum-doped phosphogypsum;

[0008] (2) mixing water and calcium aluminum phosphoglossypsum uniformly to obtain calcium aluminum phosphoglossypsum slurry;

[0009] (3) placing the calcium aluminum-doped phospho-gypsum slurry in the cathode tank of the electrolytic cell, connecting the power supply, and simultaneously exposing the carbon dioxide gas from the bottom of the cathode tank, and obtaining the anolyte from the anode tank of the electrolytic cell and the cathode slurry from the cathode tank of the electrolytic cell after 2 to 12 hours of treatment; placing a diaphragm and a sulfate anion exchange membrane in parallel between the cathode tank and the anode tank of the electrolytic cell, and the diaphragm is in direct contact with the calcium aluminum-doped phospho-gypsum slurry;

[0010] (4) filtering the anolyte to obtain a sulfuric acid aqueous solution;

[0011] (5) Drying, calcining, and grinding the cathode slurry to obtain a gelling material.

[0012] Furthermore, the mass ratio of quicklime, aluminum ash and phosphogypsum in step (1) is 2.5-12.5:10-30:100.

[0013] Furthermore, in step (2), the liquid-to-solid ratio of water to calcium aluminum phosphide gypsum is 2 to 4:1 mL / g.

[0014] Furthermore, the power supply in step (3) is a DC power supply with a current of 200 to 2000A and a voltage of 20 to 200V.

[0015] Furthermore, the carbon dioxide gas aeration rate in step (3) is 0.5 to 4.5 L / min.

[0016] Furthermore, the calcination temperature in step (5) is 1000-1600°C.

[0017] Furthermore, the calcination time in step (5) is 10 to 40 minutes.

[0018] Reaction mechanism: After water and calcium aluminum phosphogypsum are mixed, the quicklime reacts with the phosphate dissolved in the phosphogypsum, the fluoride ions, the ammonia released by the aluminum ash in the water, and aluminum hydroxide during the mixing and slurrying process to form hydroxyapatite, fluorohydroxyapatite, calcium ammonium phosphate, aluminum ammonium phosphate and other precipitates, thereby not only absorbing and stabilizing the ammonia in the aluminum ash, but also adsorbing and stabilizing the free phosphate and fluoride ions released from the phosphogypsum. The calcium aluminum phosphogypsum slurry is placed in the cathode tank of the electrolytic cell. After the power is turned on, the gypsum in the cathode tank reacts with the exposed carbon dioxide to generate calcium carbonate with lower solubility and release sulfate. At the same time, the cathode electrode continuously hydrolyzes to generate hydrogen and hydroxide. Hydrogen can achieve uniform mixing of the materials, and the hydroxide is continuously adsorbed into the calcium aluminum phosphogypsum slurry to achieve efficient alkali excitation of the calcium aluminum phosphogypsum slurry and promote the continuous generation of hydroxyapatite and the conversion of aluminum hydroxide into aluminate. The sulfate released in the cathode tank passes through the diaphragm and sulfate anion exchange membrane through electromigration, and after reaching the anode tank, it combines with the hydrogen ions generated by hydrolysis on the surface of the anode electrode to form a sulfuric acid aqueous solution. The cathode slurry is dried, calcined, and ground. During the high-temperature calcination process, hydroxide, aluminum hydroxide, calcium aluminate, hydroxyapatite, fluorohydroxyapatite, ammonium calcium phosphate, ammonium aluminum phosphate, etc. fully react with each other to form a gelling material.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following outstanding advantages: the present invention uses phosphogypsum and aluminum ash to simultaneously prepare sulfuric acid and cementitious materials, the prepared sulfuric acid aqueous solution has a maximum sulfuric acid mass fraction of 43%, and the prepared cementitious material has a maximum strength of 46.79MPa. The preparation operation process is simple and the equipment requirements are low. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0022] Phosphogypsum: Phosphogypsum was taken from a phosphate fertilizer plant in Xifeng, Guizhou. The phosphogypsum sample mainly contained 52.70% SO3, 37.01% CaO, 4.37% SiO2, 2.07% Al2O3, 1.63% P2O5 and other components.

[0023] Aluminum ash: Aluminum ash is provided by an aluminum smelting enterprise in Xinchang, mainly including 65.87% Al2O3, 8.34% Cl, 6.74% Na2O, 5.56% SiO2, 3.72% MgO, 2.46% CaO, 2.24% S, 1.86% TiO2 and other components.

[0024] Example 1 Effect of the mass ratio of quicklime, aluminum ash and phosphogypsum on the concentration of the prepared aqueous sulfuric acid solution and the strength properties of the cementitious material

[0025] According to the mass ratio of quicklime, aluminum ash and phosphogypsum: 1.25:10:100, 1.5:10:100, 2:10:100, 2.5:5:100, 2.5:6:100, 2.5:8:100, 2.5:10:100, 7.5:10:100, 12.5:10:100, 2.5:20:100, 7.5:20:100, 12.5:20:100. :100, 2.5:30:100, 7.5:30:100, 12.5:30:100, 13.5:30:100, 14.5:30:100, 15:30:100, 12.5:32:100, 12.5:34:100, 12.5:35:100, respectively weigh quicklime, aluminum ash, and phosphogypsum, mix and stir evenly to obtain calcium aluminum-doped phosphogypsum. Mix water and calcium aluminum-doped phosphogypsum at a liquid-solid ratio of 2:1 mL / g, stir evenly, and obtain calcium aluminum-doped phosphogypsum slurry. The calcium aluminum-doped phospho-gypsum slurry is placed in the cathode tank of the electrolytic cell and powered on. During the power-on process, carbon dioxide gas is simultaneously exposed from the bottom of the cathode tank. After 2 hours of treatment, anolyte is obtained from the anode tank of the electrolytic cell and cathode slurry is obtained from the cathode tank of the electrolytic cell. A diaphragm and a sulfate anion exchange membrane are placed in parallel between the cathode tank and the anode tank of the electrolytic cell, and the diaphragm is in direct contact with the calcium aluminum-doped phospho-gypsum slurry. The power supply is a DC power supply with a current of 200A and a voltage of 20V. The carbon dioxide gas aeration volume is 0.5L / min. The anolyte is filtered to obtain a sulfuric acid aqueous solution. The cathode slurry is dried, calcined, and ground to obtain a gelling material, wherein the calcination temperature is 1000°C and the calcination time is 10 minutes.

[0026] Strength performance test: The cementitious material prepared by the present invention is made into the tested mortar, the preparation of the mortar, the preparation of the test piece, the maintenance of the test piece, the selection of the test piece age and the 28-day compressive strength (P 28 The measurement of strength of cement mortar (MPa) was carried out in accordance with the standard GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The sand mixed in the preparation of the specimens was the ISO standard sand specified in GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)".

[0027] Test of sulfuric acid mass fraction of sulfuric acid aqueous solution: The sulfuric acid mass fraction of sulfuric acid aqueous solution was tested according to the national standard "Industrial Sulfuric Acid" (GB / T 534). The results are shown in Table 1.

[0028] Table 1 Effect of the mass ratio of quicklime, aluminum ash and phosphogypsum on the concentration of prepared sulfuric acid aqueous solution and the strength properties of cementitious materials

[0029]

[0030]

[0031] It can be seen from Table 1 that when the mass ratio of quicklime, aluminum ash and phosphogypsum is less than 2.5:10:100 (as in Table 1, the mass ratio of quicklime, aluminum ash and phosphogypsum = 2.5:8:100, 2.5:6:100, 2.5:5:100, 2:10:100, 1.5:10:100, 1.25:10:100 and lower ratios not listed in Table 1), the amount of quicklime and aluminum ash added is small, and the amount of cementitious material generated is small, resulting in a significant decrease in the strength of the specimen as the mass ratio of quicklime, aluminum ash and phosphogypsum decreases. When the mass ratio of quicklime, aluminum ash and phosphogypsum is equal to 2.5-12.5:10-30:100 (as in Table 1, the mass ratio of quicklime, aluminum ash and phosphogypsum = 2.5:10:100, 7.5:10:100, 12.5:10:100, 2.5:20:100, 7.5:20:100, 12.5:20:100, 2.5:30:100, 7.5:30:100, 12.5:30:100), the calcium aluminum-doped phosphogypsum slurry is placed in the cathode tank of the electrolytic cell. After the power is turned on, the gypsum in the cathode tank reacts with the exposed carbon dioxide to generate calcium carbonate with lower solubility and release sulfate. At the same time, the cathode electrode continuously hydrolyzes to generate hydrogen and hydroxide. Hydrogen can achieve uniform mixing of materials, and hydroxide is continuously adsorbed into the calcium aluminum phosphate gypsum slurry to achieve efficient alkali excitation of the calcium aluminum phosphate gypsum slurry and promote the continuous generation of hydroxyapatite and the conversion of aluminum hydroxide into aluminate. The sulfate released in the cathode tank passes through the diaphragm and sulfate anion exchange membrane through electromigration, and after reaching the anode tank, it combines with the hydrogen ions generated by hydrolysis on the surface of the anode electrode to form a sulfuric acid aqueous solution. The cathode slurry is dried, calcined, and ground. During the high-temperature calcination process, hydroxide, aluminum hydroxide, calcium aluminate, hydroxyapatite, fluorohydroxyapatite, calcium ammonium phosphate, and aluminum ammonium phosphate fully react with each other to form a cementitious material. Finally, the strength of the cementitious material is greater than 35MPa, and the mass fraction of sulfuric acid in the prepared sulfuric acid solution is greater than 26%. When the mass ratio of quicklime, aluminum ash, and phosphogypsum is greater than 12.5:10:100 (such as in Table 1, the mass ratio of quicklime, aluminum ash, and phosphogypsum = 13.5:30:100, 4.5:30:100, 5:30:100, 2.5:32:100, 2.5:34:100, 2.5:35:100, and higher ratios not listed in Table 1), the amount of quicklime and aluminum ash added is too much, resulting in a significant decrease in the strength of the cementitious material and the mass fraction of sulfuric acid in the sulfuric acid solution as the mass ratio of quicklime, aluminum ash, and phosphogypsum increases. In general, when the mass ratio of quicklime, aluminum ash, and phosphogypsum is equal to 2.5-12.5:10-30:100, it is most conducive to improving the activity of the prepared cementitious material and increasing the mass fraction of sulfuric acid in the sulfuric acid aqueous solution.

[0032] Example 2 Effect of electrolysis time on the concentration of prepared sulfuric acid aqueous solution and strength properties of cementitious materials

[0033] According to the mass ratio of quicklime, aluminum ash and phosphogypsum of 12.5:30:100, quicklime, aluminum ash and phosphogypsum are weighed respectively, mixed and stirred evenly to obtain calcium aluminum-doped phosphogypsum. According to the liquid-solid ratio of 3:1 mL / g, water and calcium aluminum-doped phosphogypsum are mixed and stirred evenly to obtain calcium aluminum-doped phosphogypsum slurry. The calcium aluminum-doped phospho-gypsum slurry is placed in the cathode tank of the electrolytic cell and powered on. During the power-on process, carbon dioxide gas is simultaneously exposed from the bottom of the cathode tank. After treatment for 0.5 hour, 1 hour, 1.5 hours, 2 hours, 7 hours, 12 hours, 13 hours, 14 hours and 15 hours, anolyte is obtained from the anode tank of the electrolytic cell and cathode slurry is obtained from the cathode tank of the electrolytic cell, respectively. A diaphragm and a sulfate anion exchange membrane are placed in parallel between the cathode tank and the anode tank of the electrolytic cell, and the diaphragm is in direct contact with the calcium aluminum-doped phospho-gypsum slurry. The powered on power is a DC power supply with a current of 1100A and a voltage of 110V. The aeration rate of carbon dioxide gas is 2.5L / min. The anolyte is filtered to obtain a sulfuric acid aqueous solution. The cathode slurry is dried, calcined and ground to obtain a gelling material, wherein the calcination temperature is 1300°C and the calcination time is 25 minutes.

[0034] The strength performance test and the sulfuric acid mass fraction test of the sulfuric acid aqueous solution are the same as those in Example 1.

[0035] Table 2 Effect of electrolysis time on the concentration of prepared sulfuric acid aqueous solution and strength properties of cementitious materials

[0036] Electrolysis time Cementitious material strength (MPa) <![CDATA[Mass fraction of sulfuric acid (H2SO4)]]> 0.5 hours 26.27 10.13% 1 hour 31.75 16.03% 1.5 hours 36.73 27.61% 2 hours 41.37 35.14% 7 hours 43.86 38.51% 12 hours 44.79 43.64% 13 hours 38.94 42.11% 14 hours 35.73 43.76% 15 hours 28.91 42.98%

[0037] It can be seen from Table 2 that when the electrolysis time is less than 2 hours (electrolysis time = 1.5 hours, 1 hour, 0.5 hours and lower values ​​not listed in Table 2), the electrolysis time is short, and the calcium aluminum phosphate gypsum slurry is not fully electrolyzed, resulting in the strength of the cementitious material and the mass fraction of sulfuric acid in the sulfuric acid solution being significantly reduced as the electrolysis time decreases. When the electrolysis time is equal to 2 to 12 hours (electrolysis time = 2 hours, 7 hours, 12 hours in Table 2), the calcium aluminum phosphate gypsum slurry is placed in the cathode tank of the electrolytic cell. After the power is turned on, the gypsum in the cathode tank reacts with the exposed carbon dioxide to generate calcium carbonate with lower solubility and release sulfate. At the same time, the cathode electrode continuously hydrolyzes to generate hydrogen and hydroxide, and hydrogen can achieve uniform mixing of the material. Hydroxide is continuously adsorbed into the calcium aluminum phosphate gypsum slurry to achieve efficient alkali excitation of the calcium aluminum phosphate gypsum slurry and promote the continuous generation of hydroxyapatite and the conversion of aluminum hydroxide into aluminate. The sulfate radical released in the cathode tank passes through the diaphragm and the sulfate anion exchange membrane through the electromigration effect, and after reaching the anode tank, it combines with the hydrogen ions generated by hydrolysis on the surface of the anode electrode to form a sulfuric acid aqueous solution. Finally, the strength of the gelling material is greater than 41MPa, and the sulfuric acid mass fraction of the prepared sulfuric acid solution is greater than 35%. When the electrolysis time is greater than 12 hours (as in Table 2, electrolysis time = 13 hours, 14 hours, 15 hours and higher values ​​not listed in Table 2), the electrolysis time is too long, and too many hydrogen ions migrate to the electrolytic cell sample area and the cathode tank, causing the gelling material strength to significantly decrease as the electrolysis time further increases. Generally speaking, when the electrolysis time is equal to 2 to 12 hours, it is most conducive to improving the activity of the prepared gelling material and improving the sulfuric acid mass fraction of the sulfuric acid aqueous solution.

[0038] Example 3 Effect of carbon dioxide aeration rate on the concentration of prepared sulfuric acid aqueous solution and strength properties of cementitious materials

[0039] According to the mass ratio of quicklime, aluminum ash and phosphogypsum of 12.5:30:100, quicklime, aluminum ash and phosphogypsum are weighed respectively, mixed and stirred evenly to obtain calcium aluminum doped phosphogypsum. Water and calcium aluminum doped phosphogypsum are mixed according to the liquid-solid ratio of 4:1mL / g, stirred evenly, and calcium aluminum doped phosphogypsum slurry is obtained. The calcium aluminum doped phosphogypsum slurry is placed in the cathode tank of the electrolytic cell, and the power is turned on. During the power-on process, carbon dioxide gas is simultaneously exposed from the bottom of the cathode tank. After 12 hours of treatment, the anolyte is obtained from the anode tank of the electrolytic cell, and the cathode slurry is obtained from the cathode tank of the electrolytic cell, wherein a diaphragm and a sulfate anion exchange membrane are placed in parallel between the cathode tank and the anode tank of the electrolytic cell, and the diaphragm is in direct contact with the calcium aluminum doped phosphogypsum slurry; wherein the power supply connected is a DC power supply, the current is 2000A, and the voltage is 200V. The aeration rate of carbon dioxide gas is 0.25L / min, 0.3L / min, 0.4L / min, 0.5L / min, 2.5L / min, 4.5L / min, 5L / min, 5.5L / min and 6L / min; the anode liquid is filtered to obtain an aqueous solution of sulfuric acid; the cathode slurry is dried, calcined and ground to obtain a gelling material, wherein the calcination temperature is 1600°C and the calcination time is 40 minutes.

[0040] The strength performance test and the sulfuric acid mass fraction test of the sulfuric acid aqueous solution are the same as those in Example 1.

[0041] Table 3 Effect of carbon dioxide aeration rate on the concentration of prepared sulfuric acid aqueous solution and strength properties of cementitious materials

[0042]

[0043]

[0044] It can be seen from Table 3 that when the carbon dioxide gas aeration rate is less than 0.5L / min (such as in Table 3, electrolysis time = 0.4L / min, 0.3L / min, 0.25L / min and lower values ​​not listed in Table 3), the carbon dioxide gas aeration rate is small, and the sulfate release rate is reduced, resulting in the strength of the cementitious material and the sulfuric acid mass fraction of the sulfuric acid solution being significantly reduced as the carbon dioxide gas aeration rate decreases. When the carbon dioxide gas aeration rate is equal to 0.5-4.5L / min (such as in Table 3, electrolysis time = 0.5L / min, 2.5L / min, 4.5L / min), after the power is turned on, the gypsum in the cathode tank reacts with the exposed carbon dioxide to generate calcium carbonate with lower solubility and release sulfate. At the same time, the cathode electrode continuously hydrolyzes to generate hydrogen and hydroxide, and hydrogen can achieve uniform mixing of the material, and the hydroxide is continuously adsorbed into the calcium aluminum phosphate-doped gypsum slurry to achieve efficient alkali excitation of the calcium aluminum phosphate-doped gypsum slurry and promote the continuous generation of hydroxyapatite and the conversion of aluminum hydroxide into aluminate. The sulfate released in the cathode tank passes through the diaphragm and the sulfate anion exchange membrane by electromigration, and after reaching the anode tank, it combines with the hydrogen ions generated by hydrolysis on the surface of the anode electrode to form a sulfuric acid aqueous solution. Finally, the strength of the gelling material is greater than 42MPa, and the sulfuric acid mass fraction of the prepared sulfuric acid solution is greater than 38%. When the carbon dioxide gas aeration amount is greater than 4.5L / min (as in Table 3, electrolysis time = 5L / min, 5.5L / min, 6L / min and higher values ​​not listed in Table 3), excessive bicarbonate is generated, so that the sulfate release efficiency is reduced, and too much bicarbonate enters the anode tank and the slurry, resulting in the gelling material strength and the sulfuric acid mass fraction of the sulfuric acid solution are significantly reduced as the carbon dioxide gas aeration amount further increases. In general, when the carbon dioxide gas aeration amount is equal to 0.5-4.5L / min, it is most conducive to improving the activity of the prepared gelling material and improving the sulfuric acid mass fraction of the sulfuric acid aqueous solution.

Claims

1. A method for synchronously preparing sulfuric acid and cementitious material using phosphogypsum and aluminum ash, characterized in that: The following steps are involved: (1) Mix quicklime, aluminum ash and phosphogypsum and stir them evenly to obtain calcium aluminum-doped phosphogypsum; The mass ratio of quicklime, aluminum ash and phosphogypsum is 2.5-12.5:10-30:100; (2) mixing water and calcium aluminum doped phosphogypsum uniformly to obtain calcium aluminum doped phosphogypsum slurry; (3) placing the calcium aluminum-doped phosphogyes slurry in the cathode tank of the electrolytic cell, connecting the power supply, and simultaneously exposing the carbon dioxide gas from the bottom of the cathode tank. After 2 to 12 hours of treatment, obtaining the anolyte from the anode tank of the electrolytic cell and obtaining the cathode slurry from the cathode tank of the electrolytic cell; placing a diaphragm and a sulfate anion exchange membrane in parallel between the cathode tank and the anode tank of the electrolytic cell, and the diaphragm is in direct contact with the calcium aluminum-doped phosphogyes slurry; (4) filtering the anolyte to obtain an aqueous solution of sulfuric acid; (5) Drying, calcining, and grinding the cathode slurry to obtain a gelling material.

2. The method according to claim 1, characterized in that The liquid-to-solid ratio of water to calcium aluminum phosphide gypsum in step (2) is 2-4:1 mL / g.

3. The method according to claim 1, characterized in that The power supply in step (3) is a DC power supply with a current of 200-2000A and a voltage of 20-200V.

4. The method according to claim 1, characterized in that: The carbon dioxide gas aeration rate in step (3) is 0.5~4.5L / min.

5. The method according to claim 1, characterized in that The calcination temperature in step (5) is 1000-1600°C.

6. The method according to claim 1, characterized in that The calcination time in step (5) is 10 to 40 minutes.